Edukasi dan Pelatihan Pengelolaan Keuangan UMKM dan Organisasi melalui Implementasi Buku Kas Sederhana di Dusun Gandari, Lombok Barat - I Gede Yogi Januartha; Ni Wayan Rasmini; Wihelmus Jemarut; I Komang Widya Purnama Yasa (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was carried out in Gandari Hamlet, Narmada Village, Narmada District, West Lombok Regency, West Nusa Tenggara Province, with the aim of improving financial literacy and financial management skills of micro business actors and local organizations through the implementation of a simple cash book system. This activity was motivated by low public awareness of financial recording and weak cash flow management practices. The implementation of the program uses a participatory and educational approach which is carried out through three stages, namely observation and identification of financial problems, education and training in the use of simple cash books, and evaluation and assistance in the implementation of financial records. Data collection was carried out through field observations, interviews, and questionnaires involving ten participants. The results of the activity showed that most of the participants had not previously made written financial records. After the training, as many as 60% of participants began to record daily transactions consistently, while 70% stated that simple cash books are easy to use and beneficial for business management. This program has succeeded in fostering financial awareness, discipline, and accountability among participants, as well as encouraging the creation of sustainable financial practices and empowering local micro-enterprises to be more transparent and independent.